Remains of the homestead from the Late Bronze Age discovered in Ruda (Northern Poland) in the light of pedoarchaeological studies - Markiewicz, Maciej (Bulletin of Geography. Physical Geography Series, 2016)
On the basis of archaeological data and pedological analysis an attempt of reconstruction of functional diversity of farmstead from the Late Bronze Age in northern Poland was made. Human activity during the Late Bronze Age in the area and in the direct vicinity of the homestead led to changes in chemical properties of the soil. Different values of phosphorus and organic carbon content in the features and cultural layers may help in the interpretation of the land development plan and the use of the studied households in the past. The areas with the highest concentration are linked with the places of economic activity and a small increase in the phosphorus content in the soil from the homestead may suggest a relatively short exploitation of this place corresponding with a small number of archaeological findings from the analysed area. The current state of knowledge about the open settlements from the Late Bronze Age in the territory of Poland does not provide too many analogies with the previously described homestead. Because similar spatial assumptions are also known from the Carpathian Highlands as well as from the north – German and the south – Scandinavian terrains, we may draw a conclusion that the knowledge of this type of construction reached people living in Ruda’s surroundings as a result of contacts from the Southern or Eastern Europe.